Peranan Komunikasi Bisnis Dalam Meningkatkan Minat Beli Konsumen Pada Pasar Modern Sinpasa Summarecon - Amelia Putri Anggraeni; Fikri Mutawalli Dinullah; Mochammad Rhizal Divawan; Rika Malinda; Saudah Putri Saffana; Selly Nuryani; Ricky Firmansyah (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2023)
The business world of communication is an important element in delivering product information, an entrepreneur needs to make his target understand his product. Not only in product delivery, an entrepreneur must be good in his communication skills, both expressing ideas and ideas. The purpose of this study is to find out the role of business communication to facilitate economic progress at the Summarecon Sinpasa Modern Market, for residents who have businesses, open shops, kiosks or places to eat, where the Summarecon Sinpasa Modern Market it has 117 tenants. This research method was carried out using qualitative methods, qualitative methods are research methods using descriptive data in the form of writing or oral, this qualitative method is to analyze individual or group phenomena, events. According to Lexy J Moleong. After conducting research at the Summarecon Sinpasa Modern Market through qualitative research we have analyzed it by conducting interviews with 15 traders there. So the results that we get are the factors of increasing consumer buying interest in the Summarecon Sinpasa Modern Market, namely, good service quality, customer satisfaction, product quality, and price. The role of business communication can also develop solutions that help traders to develop their business and can solve the problems they face.